Addressing Cryptographic Overheads in Low-Latency File Systems Through Ahead-of-Time Encryption - Correia, Jorge Pires; Zola, Wagner Machado N. (Anais do Latin-American Symposium on Dependable Computing (LADC); 2025: Anais do XIV Latin-American Symposium on Dependable Computing, 2025)
Historically, the high latency of storage devices masked the impact of software overheads in the storage stack. However, with the advent of microsecond-scale storage devices, the performance cost of adding new software layers has become more significant. In particular, integrating cryptographic operations into file systems that run on low-latency devices poses substantial challenges. This paper investigates the application of ahead-of-time and speculative encryption techniques to in-kernel file systems, tailored for modern storage devices. Our experimental results demonstrate that these techniques significantly improve both latency and throughput, outperforming current cryptographic file systems.